Incidencia del microcrédito en el crecimiento en las microempresas agroproductivas de Manabí - Chávez Zambrano, Stefanía Elizabeth (2019)
The purpose of this study was to evaluate the incidence of microcredits in the growth of agroproductive microenterprises in Manabí providence. For this purpose, a nonexperimental, descriptive and field study was implemented, carrying out an interview with the officials of the financial entities responsible for the granting of microcredits and a survey addressed to microentrepreneurs. It was possible to characterize the conditions used in the granting of microcredits, evidencing the office and field process inherent in the placement of loans. It was identified that the financial institutions with the highest volume of microcredits granted in Manabí providence are the Pichincha bank, Guayaquil bank and Solidario bank. These banks grant loans from USD 300 to USD 20,000, with interest rates between 11.23 and 28.5% and terms from 2 to 48 months. It was also determined that microcredits were mainly invested in the rearing of cattle or other animals, that the amounts most frequently borrowed range from USD 1000 and USD 3000 and that the largest proportion of microenterprises used the loan for the maintenance of the business, that is, capitalization, repowering or agricultural correction of the productive system. Finally, an effective correlation was evidenced in the business acquisition of technological equipment for the improvement of production processes and the increase in productivity (Pearson's Chi-square 0.00) and the economic situation of the microenterprises benefited (Chi-square of Pearson 0.007).